Librarianship and information science in the Islamic world, 1966-1999 an annotated bibliography - Coleman, Sterling Joseph 1969- (Scarecrow Press, 2005)
Country-by-country, this comprehensive, annotated bibliography brings together the vast number of articles, books, conference papers, theses and dissertations, and reports that have been written about librarianship in the Islamic World during the past fifty years